2014
DOI: 10.1007/s12032-014-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of TRIM3 is associated with poor prognosis in patients with primary hepatocellular carcinoma

Abstract: Tripartite motif-containing 3 (TRIM3) is a member of the tripartite motif (TRIM) protein family and is reported to be involved in the pathogenesis of various cancers. The role of TRIM3 in hepatocellular carcinoma (HCC) is unknown; thus, the goal of this study was to explore the expression level and prognostic value of TRIM3 in HCC. The expression level of TRIM3 in HCC surgically resected tumors and corresponding nontumorous samples was detected by real-time quantitative RT-PCR, Western blotting, and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
2
18
0
2
Order By: Relevance
“…Contrarily, silencing TRIM3 promoted cell motility. These findings were consistent with the results of our clinicopathologic analysis, which showed that low TRIM3 expression was significantly associated with advanced tumor stage [ 25 ]. Furthermore, we performed in vivo metastasis assay in nude mice to investigate whether TRIM3 overexpression could alter the in vivo metastatic ability of liver cancer cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Contrarily, silencing TRIM3 promoted cell motility. These findings were consistent with the results of our clinicopathologic analysis, which showed that low TRIM3 expression was significantly associated with advanced tumor stage [ 25 ]. Furthermore, we performed in vivo metastasis assay in nude mice to investigate whether TRIM3 overexpression could alter the in vivo metastatic ability of liver cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…TRIM3 overexpression in HepG2 and Bel-7402 cells significantly delayed tumor growth in mice. These results were in line with our clinical findings that the low level of TRIM3 was significantly associated with large tumors [ 25 ]. Consistent with our results, previous studies also demonstrated that TRIM3 overexpression inhibited glioma cell proliferation and tumor growth [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, opposing effects of aberrant TRIM expression on carcinogenesis can occur ranging from oncogenic to mainly tumor-suppressive effects depending on the protein targeted by the respective TRIM. While the majority of TRIM proteins have been assigned to act mainly as oncogenes due to the bad prognosis and outcome of patients with high tissue expression levels of the corresponding TRIM protein, only a few members including TRIM3 [ 33 ], TRIM8 [ 34 ], TRIM15 [ 35 ], TRIM45 [ 36 ], TRIM58 [ 37 ], and TRIM68 [ 38 ] can elicit tumor suppressive activities. In accordance, some of these tumor suppressive TRIM members are downregulated in CRC [ 39 ].…”
Section: Introductionmentioning
confidence: 99%